Building work-related knowledge about examination invigilation through reflective journaling. Issue 2 (30th January 2020) - Minott, Mark
Abstract : Purpose: The purpose of the self-study is two-fold: first, to aid in redressing the lack of attention given to the professional development i.e., the building of practical or work-related knowledge of examination invigilators and second, to forward the idea that engaging the examination invigilation process reflectively is an effective form of self-directed professional development. Design/methodology/approach: The report uses reflective journaling based on Minott (2017) reflective approach to teaching practicum debriefing strategy to show the practical or work-related knowledge built by the author. Findings: The report shows how the author built practical or work-related knowledge about critical aspects of the invigilation process: adaptability/flexibility, leading humanely and "thinking on your feet"/reflection-in-action. Originality/value: This paper shows (through a critical discussion of the literature, coupled with the author's personal professional experiences displayed in reflective journal entries) that an attitude of self-directed inquiry combined with reflective journaling can enable professional development i.e. the development of practical or work-related knowledge.